2003
DOI: 10.1128/cdli.10.3.399-404.2003
|View full text |Cite
|
Sign up to set email alerts
|

TH1 and TH2 Cytokine mRNA and Protein Levels in Human Immunodeficiency Virus (HIV)-Seropositive and HIV-Seronegative Youths

Abstract: The roles of cytokines in the progression of human immunodeficiency virus (HIV)-associated disease are controversial. The patterns of innate cytokine production have been postulated to shift from TH1-to TH2-type cytokines with the progression of HIV-associated disease. Although there have been studies of cytokines in children and adults, no data are available on cytokine production in healthy or HIV-infected adolescents. We analyzed and characterized cytokine mRNA and protein levels for gamma interferon, inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
(23 reference statements)
1
12
0
1
Order By: Relevance
“…The results were highly reproducible (coefficients of variation <20% in >80% of test samples). Testing of the first eight analytes was based on (1) initial screening of 42 analytes (representing T H 1 and T H 2 cytokines, C-X-C and C-C motif chemokines, growth factors, as well as markers of inflammation and angiogenesis) using the Human Cytokine Array III (RayBiotech Inc., Norcross GA), 33 (2) dismissal of IFN-g, IL-2, IL-4, IL-6, and tumor necrosis factor alpha (TNF-a) as informative markers of HIV-1 pathogenesis in the REACH cohort, 34 (3) analysis of serum samples from the REACH cohort, 26 and (4) successful quantification in over 90% of samples from HIV-1 þ youth. Inclusion of C-reactive protein (CRP) was based on its frequent recognition as a reliable marker of chronic inflammation related to various immune disorders.…”
Section: Multiplexing Enzyme-linked Immunosorbent Assay (Searchlight)mentioning
confidence: 99%
“…The results were highly reproducible (coefficients of variation <20% in >80% of test samples). Testing of the first eight analytes was based on (1) initial screening of 42 analytes (representing T H 1 and T H 2 cytokines, C-X-C and C-C motif chemokines, growth factors, as well as markers of inflammation and angiogenesis) using the Human Cytokine Array III (RayBiotech Inc., Norcross GA), 33 (2) dismissal of IFN-g, IL-2, IL-4, IL-6, and tumor necrosis factor alpha (TNF-a) as informative markers of HIV-1 pathogenesis in the REACH cohort, 34 (3) analysis of serum samples from the REACH cohort, 26 and (4) successful quantification in over 90% of samples from HIV-1 þ youth. Inclusion of C-reactive protein (CRP) was based on its frequent recognition as a reliable marker of chronic inflammation related to various immune disorders.…”
Section: Multiplexing Enzyme-linked Immunosorbent Assay (Searchlight)mentioning
confidence: 99%
“…Another γ C cytokine whose production is increased in HIV infection is IL‐4 83 , 84 , 85 , 86 , 87 . It is thought that IL‐4‐mediated Th2 responses contribute to the onset of AIDS 88 .…”
Section: Expression and Regulation Of γC Receptors In Health And Hiv mentioning
confidence: 99%
“…Type 1 cytokines, generally, are decreased with the progression of HIV disease, whereas type 2 cytokines are increased. However, some authors have shown that there are no detectable shifts from Th1 to Th2 cytokine production in HIV infection [14,15]. Little is known in the literature about IL-15 production in HIVinfected individuals.…”
Section: Il-15 Production During Hiv Infectionmentioning
confidence: 93%